Hydrogen Sulfide Ameliorates Homocysteine-Induced Cardiac Remodeling and Dysfunction - Kar, Sumit; Shahshahan, Hamid R.; Kambis, Tyler N.; Yadav, Santosh K.; Li, Zhen; Lefer, David J.; Mishra, Paras K. (Frontiers in Physiology, 2019)
Patients with diabetes, a methionine-rich meat diet, or certain genetic polymorphisms show elevated levels of homocysteine (Hcy), which is strongly associated with the development of cardiovascular disease including diabetic cardiomyopathy. However, reducing Hcy with folate shows no beneficial cardiac effects. We have previously shown that hydrogen sulfide (H₂S), a byproduct of Hcy through transsulfuration by cystathionine beta synthase (CBS), donor mitigates Hcy-induced hypertrophy in cardiomyocytes. However, the in vivo cardiac effects of H₂S in the context of hyperhomocysteinemia (HHcy) have not been studied. We tested the hypothesis that HHcy causes cardiac remodeling and dysfunction in vivo, which is ameliorated by H₂S. Twelve-week-old male CBS+/- (a model of HHcy) and sibling CBS+/+ WT mice were treated with SG1002 (a slow release H₂S donor) diet for four months. The left ventricle of CBS+/- mice showed increased expression of early remodeling signals c-Jun and c-Fos, increased interstitial collagen deposition, and increased cellular hypertrophy. Notably, SG1002 treatment reduced c-Jun and c-Fos expression, decreased interstitial fibrosis, and mitigated cellular hypertrophy. Pressure-volume loop analyses in CBS+/- mice revealed increased end-systolic pressure with no change in stroke volume (SV) suggesting increased afterload, which was abolished by SG1002 treatment. Additionally, SG1002 treatment increased end-diastolic volume and SV in CBS+/- mice, suggesting increased ventricular filling. These results demonstrate SG1002 treatment alleviates cardiac remodeling and afterload in HHcy mice. H₂S may be cardioprotective in conditions where H₂S is reduced and Hcy is elevated.